Production of biodiesel from waste shark liver oil for biofuel applications. (January 2020) - Al Hatrooshi, Ahmed Said; Eze, Valentine C.; Harvey, Adam P.
Abstract: Biodiesel is a renewable alternative to "petro-diesel". There is an established conventional production technology based on refined vegetable oils. However, this is always more expensive than petroleum-based diesel, mainly due to the feedstock cost, and the biodiesel market is based on subsidies. Use of a cheap non-edible feedstock, such as waste shark liver oil (WSLO), would reduce the biodiesel production cost and make the process more economically viable. In this study, production of fatty acid methyl ester (FAME) from WSLO using both acid (H2 SO4 ) and base (NaOH) catalysts were investigated using a Design of Experiments approach (response surface methodology). Due to the high levels of FFA (free fatty acids) homogeneous alkali-catalysed transesterification of WSLO was less effective than the acid-catalysed process, resulting in WSLO to FAME conversion of 12% after 60 min, with maximum FAME conversion of about 40% after 15 min. Acid-catalysed WSLO transesterification achieved 99% FAME conversion at 10.3 M ratio of methanol to WSLO, 6.5 h reaction time, 60 °C temperature, and 5.9 wt % of H2 SO4 catalyst. Highlights: FAME productions using WSLO Carcharhinidae family has been investigated. NaOH-catalysed process achieved only 40% FAME due to high FFA content of the WSLO. Maximum FAME conversion of 99.0 ± 1.1%, was achieved with H2 SO4 catalyst. Optimal FAME conversion occurred at 10.3:1 methanol molar ratio, 6.5 h and 5.9 wt% H2SO4.